A high-frequency wearable IMU-based system for countermovement jump assessment - Pousibet-Garrido, A.; Benavente, C.; Moreno-Pérez, J. A.; Pérez-Regalado, S.; Carvajal, M. A.; Chirosa, I. J.; Escobedo, P. (Sensors, 2026)
What are the main findings?